OPTIMUM STRATEGY FOR HIGLIWAY RECONSTRUCTION - I. M. Tsarenkova; T. R. Kisel (Наука и техника)
The paper is devoted to development of scientific and methodological principles and practical recommendations on highway reconstruction with the purpose to remove existing speed limitations. A system approach is used in the paper; pre-requisites for increasing automobile speed in the international transport corridors within the territory of the Republic of Belarus are take into account. In order to solve the problem the paper proposes an index of investment utilization which makes it possible scientifically to substantiate and determine the most important sections for removing speed limitations at some directions of international transport corridors, and model of its calculation. A mathematical model has been developed to select optimum strategy for highway reconstruction. The proposed methodology for stage-by-stage execution of highway reconstruction can be used at any section of a highway with the purpose to determine minimum investment and maximum reduction in automotive operational time. Its application gives an optimum variant of a highway reconstruction